ETHNOGRAPHIC STUDY OF THE CHARACTER OF MADRASAH IBTIDAIYAH STUDENTS ON EXPLORATION-BASED ENVIRONMENTAL LEARNING ON THE POLLUTED BEACH OF KESENDEN CITY OF CIREBON - Puspitasari, Ratna; Resmalasari, Septiani (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
Kesenden Beach is one of the beaches located in Cirebon City. This beach has considerable tourism potential, but the environmental conditions are polluted. This is a challenge for educators to conduct environmental learning on the beach. This study aims to examine ethnographic studies on the character of Madrasah Ibtidaiyah students in environmental learning at the Polluted Kesenden Beach, Cirebon City. The method used in this research is character ethnography. Research data was obtained through observation, interviews, and documentation. The study results show that environmental learning at Kesenden Polluted Beach, Cirebon City, can increase students' awareness of the importance of protecting the environment. In addition, this learning can also instil positive characteristics in students, such as caring for the environment, responsibility, and cooperation.